2003
DOI: 10.1007/bf02711183
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and piezoelectric properties of neodymium oxide doped lead zirconate titanate ceramics

Abstract: The dielectric and electromechanical properties of lead zirconate titanate [Pb(Zr, Ti)O 3 ] ceramic added with neodymium oxide have been systematically studied employing the vector impedance spectroscopic (VIS) technique. The specimens were prepared using the mixed oxide route by adding different mol% of Nd 2 O 3 (0⋅ ⋅1 to 7 mol%) in [Pb(Zr, Ti)O 3 ] near morphotropic phase boundary. Piezoelectric equivalent circuit parameters R, L, C a in series and C b in parallel have been determined by simulating /Z/ and Θ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Our results agree very well with Thamjaree et al [19]. The results are comparable with the literature [16][17][18][19][20][21][22]. Fig.…”
Section: Microstructural Characterizationsupporting
confidence: 95%
See 1 more Smart Citation
“…Our results agree very well with Thamjaree et al [19]. The results are comparable with the literature [16][17][18][19][20][21][22]. Fig.…”
Section: Microstructural Characterizationsupporting
confidence: 95%
“…It has been observed that electromechanical properties enhance with Nd dopant concentration. As per Singh et al [21], electromechanical parameters of Nd-doped PZT (54/46 Zr/Ti ratio near MPB) significantly enhanced. In our study, maximum values of d 33 (549 pC/N) and k p (0.541) are found in 1 mol% Nd-doped PLZNT ceramic.…”
Section: Ferroelectric Characterizationmentioning
confidence: 73%
“…Effects of rare earth elements (RE) doping on the phase formation and electrical properties of piezoelectric ceramics such as barium titanate and lead zirconate titanate are well studied [12][13][14][15]. The effect of RE addition on the PMN system has also been studied in the literature to a degree.…”
Section: Introductionmentioning
confidence: 99%
“…5. It appears that the as-prepared sample is well-crystallized Nd(OH) 3 , which upon further heat treatment transformed into cubic neodymium oxide. The particles of neodymium hydroxide (seen in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…as phosphors providing yellow-to-violet upconversion emission [1]), as components for advanced materials (e.g. high temperature ceramics and superconductors) [2,3], as components of catalytic systems (oxidative coupling of methane, N 2 decomposition, dehydrogenation of alcohols, high-temperature processes) [4][5][6] and in many special applications (among others, to simulate the actinide oxides during testing the new materials as a host matrix for long life nuclear wastes [7]). Moreover, thin films of Nd 2 O 3 are of interest for many other purposes such as optical antireflection coatings, gate insulators and protective coatings.…”
Section: Introductionmentioning
confidence: 99%